Reflections on Key Issues of the Professional Responsibilities of Corporate Lawyers in the Twenty-First Century - E. Norman Veasey (Washington University Journal of Law & Policy, 2003)
This essay addresses various questions concerning corporate governance and ethical issues. The paper gives particular attention to state corporation law, standards of conduct, the business judgment rule, fiduciary duties, director independence, as well as issues of federalism.
Keywords: Corporate governance; Legal ethics; Corporations; Social responsibility; States; United States